EARNING MANAGEMENT, STOCK RETURN AND COMPANIES’ MERGER AND ACQUISITION - Sigit Handoyo; Fitria Rahmadani Putri (University of Merdeka Malang, 2015)
The purpose of this study was to find out the practice earning management before merger and acquisition announcement. It also aimed to examine the differences of stock return before and after merger and acquisition announcement among companies that were listed on Indonesia stock exchange. The samples were 35 companies that did merger and acquisition and listed in Indonesia Stock Exchange (IDX) period 2004–2013. Then, the data analysis was performed by computer statistic program SPSS. These samples were selected by using purposive sampling method. Analysis hypothesis used Independent sample t-test and Wilcoxon sign ranks test. The result of independent sample t-test showed that the companies tended to do earning management before merger and acquisitions. While the result of Wilcoxon signed ranks test showed that there was no difference between stock return before and after merger and acquisition announcement.